Penerapan Audit Operasional untuk Efektivitas dan Efisiensi Pengendalian Internal Kas pada Klinik XYZ - Harared, Bunga Anisah; Murdhaningsih, Murdhaningsih; Heriyanto, Riyan Pratama (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to conduct an operational audit at XYZ Clinic to evaluate the effectiveness of internal controls related to cash receipts and disbursements activities. The research methodology involves data collection through observation, document searches, and interviews with clinic management. Preliminary audit is carried out using the Internal Control Questionnaire (ICQ) to assess internal controls. The results of the ICQ evaluation show an effectiveness of internal controls at 59.34%. Weaknesses in internal control are identified, including the absence of written policies and procedures related to cash, and insufficient supporting documents. Analysis of the findings generates recommendations for improving internal controls in cash receipts and disbursements activities at XYZ Clinic. This research concludes that the company needs to enhance cash management through more structured and effective measures.